‘‘We” are familiar but ‘‘It” is not: Ingroup pronouns trigger feelings of familiarity - Housley, Meghan K. (2012)
The notion that language can shape social perception has a long history in psychology. The current work adds to this literature by investigating the relationship between ingroup-designating pronouns and perceptions of familiarity. In two experiments, participants were exposed to nonsense syllables that were primed with ingroup (e.g., we) and control (e.g., it) pronouns before perceptions of the syllables’ familiarity (Experiments 1 and 2) and positivity (Experiment 2) were assessed. Because previous work has shown that ingroup pronouns are perceived positively (Perdue, Dovidio, Gurtman, & Tyler, 1990), and that positivity can trigger familiarity (e.g., Garcia-Marques, Mackie, Claypool, & Garcia-Marques, 2004; Monin, 2003), we predicted that syllables primed with ingroup-designating pronouns would be perceived as more familiar and positive than would syllables primed with control pronouns. These predictions were confirmed. Additionally, Experiment 2 provided suggestive evidence that the effect of ingroup pronouns on perceived familiarity is mediated by positivity. Implications of these results for the literatures on how language shapes intergroup biases and on how positivity triggers feelings of familiarity are discussed.